Palliative Care for Cancer: A Public Health Challenge in India - Shrikant Atreya; Purushottam A Giri (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Palliative care is an emerging discipline worldwide which focuses on improving the quality of life of patients with chronic life threatening condition like cancer. Globally, palliative care is sparsely distributed in developing countries including India where the need is immense. While there is extensive coverage of this issue in palliative care literature, there is limited coverage in public health literature, which suggests that the challenges of palliative care have not been generally recognized as a priority in public health. The present article will embark upon various challenges and solutions for implementing palliative care in the country. By considering this discipline in the fi eld of public health literature, it is hoped to raise awareness and stimulate thoughts among public health professionals and health policy makers. In addition to this, a model based on preexisting research has been proposed, that will facilitate palliative care services to be delivered through the existing health care system, which will not only be accessible to the needy in remote parts of the country, but also at a cost the community and country can afford.